Advances in flap surgical techniques and regenerative approaches for reconstruction of extensive defects in cutaneous squamous cell carcinoma: a systematic review of functional and aesthetic outcomes - Ospina, Diego Román Zapata; Ruiz, Shanice Osmara Carrasco; Galindo, Andres Santodomingo; Javier, Alvarez Arroyo José; Pacheco, Elizabeth Arellano; García, María Fernanda Rojas; Bernal, Juan Gabriel Torres (International Journal of Research in Medical Sciences, 2024)
About 20–30% of non-melanoma skin malignancies globally are cutaneous squamous cell carcinomas (cSCCs). Achieving the best functional and cosmetic results in complex and Long-term instances that need rebuilding is extremely difficult. Though they lack a thorough assessment of their efficacy but recent developments in flap surgery and regenerative medicines present encouraging alternatives. We only included papers which are published between 2000-2024 were included in the preferred reporting items for systematic reviews and meta-analyses (PRISMA) -guided systematic review. Data were taken from 45 studies with 3,560 individuals (9 RCTs, 20 cohort studies, and 11 case series). Functional recovery, cosmetic satisfaction, and the rates of complications for both regenerative (such as platelet-rich plasma [PRP] and bioengineered scaffolds) and advanced flap techniques like perforator and free tissue flaps were evaluated. The Newcastle-Ottawa scale and the ROB 2 tool were used to evaluate the risk of bias. Compared to pedicled flaps (7.2/10, p<0.01), perforator flaps showed a 96.5% success rate and better functional recovery (mean mobility score: 8.5/10). Although free tissue transfers had a greater rate of complications (18%) but they produced the greatest aesthetic satisfaction scores (85%). Regenerative techniques enhanced wound healing by 25% and decreased infection rates by 15% (p=0.04). Graft survival was increased to 90% with bioengineered scaffolds as opposed to 75% without them. Complication rates were 20% overall but in high-risk instances, regenerative treatments reduced them to 10%. After all research, we can conclude that for cSCC reconstruction, the combination of regenerative procedures and sophisticated flap techniques minimizes problems while optimizing functional and aesthetic results. Free tissue transfers are favored for cosmetic reasons however perforator flaps are excellent for functional recovery. Regenerative methods like PRP and scaffolds can enhance surgical outcomes and durability.